Investigation of S.limacinum microalgae digestibility and production of antioxidant bioactive peptides. (15th January 2022) - Moaveni, Shahrzad; Salami, Maryam; Khodadadi, Maryam; McDougall, Michael; Emam-Djomeh, Zahra
Abstract: Schizochytrium limacinum ( S. limacinum ) has potential as a high protein food ingredient. The digestibility of this protein was performed in the conditions of simulated stomach phase (with pepsin enzyme) and simulated small intestine phase (with α-chymotrypsin and trypsin). The whole hydrolysate was fractionated into various ranges of molecular weight cutoff (MWCO) by using ultrafiltration (UF) technique. Antioxidant activities of hydrolysate fractions were evaluated using direct free radical scavenging activity such as 2, 2-diphenyl-1-picrylhydrazyl Radical (DPPH) scavenging, activity, 2, 2-azino-bis(3-ethylbenzthiazoline)-6-sulfonic acidradical cation (ABTS+) sscavengin activity and reducing power activity. In addition, the protective effect of purified peptide against oxidation of low-density lipoprotein (LDL) was determined. The microalgae proteins were completely hydrolyzed by digestive enzymes and the enzymatic hydrolysis of proteins resulted in increased antioxidant activity of peptides. The peptide fraction F3 (MWCO = 5–10 kDa) presented the highest antioxidant activity out of all the methods described. The protein hydrolysates showed higher reducing power, radical scavenging capacity and significantly inhibited LDL oxidation. These results suggest that the enzymatic hydrolysates from S. limacinum can act as novel antioxidants in functional foods. Graphical abstract: Image 1 Highlights: Bioactive peptides from of Schizochytrium limacinum were produced. The microalgae proteins showed good digestibility. Antioxidant activities of hydrolysate fractions were evaluated. Schizochytrium limacinum proteins can be used in production of functional foods.